2020
DOI: 10.1097/aog.0000000000004199
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Antibodies at Delivery in Women, Partners, and Newborns

Abstract: OBJECTIVE: To investigate the frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in parturient women, their partners, and their newborns and the association of such antibodies with obstetric and neonatal outcomes. METHODS: From April 4 to July 3, 2020, in a single university hospital in Denmark, all parturient women and their partners were invited to participate in the study, along with their newborns. Participating wom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 9 publications
7
36
2
1
Order By: Relevance
“…Perinatal results are reassuring, and no neonatal complications were associated with maternal SARS-COV-2 infection in previous studies [ 15 , 16 ]. Egerup et al [ 25 ] also found no differences between patients with positive versus negative antibodies in neonatal complications. We found no significant differences in APOs among our three groups, and none of the neonatal infections were by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal results are reassuring, and no neonatal complications were associated with maternal SARS-COV-2 infection in previous studies [ 15 , 16 ]. Egerup et al [ 25 ] also found no differences between patients with positive versus negative antibodies in neonatal complications. We found no significant differences in APOs among our three groups, and none of the neonatal infections were by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Egerup et al [ 25 ] studied a population of 1313 pregnant women, in Copenhagen (Denmark), from April to July 2020, including 28 cases of positive antibodies and one case of positive PCR. The study concluded that SARS-CoV-2 infection was not associated with obstetric complications in pregnant women who had had the disease.…”
Section: Discussionmentioning
confidence: 99%
“…One other study, in which SARS-CoV-2 infection during pregnancy was evaluated using antibody testing in a Danish sample, did not find a difference in CD rate between antibody positive and negative women. However, the absolute number of seropositive women in that study was low (n=28) 41 . Our findings may be influenced by the small sample size, variation in clinical practice, or unmeasured confounding factors.…”
Section: Resultsmentioning
confidence: 73%
“…As for other viruses, passive IgG acquired in utero declines in the newborn blood gradually over a 4-8-month period, whereas breast milk sIgA is likely to be secreted over a long period during the breastfeeding course. SARS-CoV-2specific data would be welcome, and preliminary information on newborn antibody presence has recently emerged [163,226,305]. One such study did not find differences in neonatal outcome after maternal infections with the presence or absence of acquired IgG antibody [305].…”
Section: Controversies With Breast Milkmentioning
confidence: 99%